The Interdisciplinary Research Team not the Interdisciplinarist - Shanker , Shanti; Wasti , Sharada Prasad; Ireland, Jillian; Regmi, Pramod Raj; Simkhada, Padam Prasad; Teijlingen, Edwin van (Europasian Journal of Medical Sciences, 2021)
Worldwide there is a growing interest in multidisciplinary and interdisciplinary research. This overview paper addresses some of the pitfalls and barriers to being an interdisciplinary researcher. Being involved in interdisciplinary research is not an easy option for an individual discipline expert. It requires individual skills, ability to see beyond one’s discipline and perhaps personality characteristics such as a great team player. Interdisciplinary research may involve a mixed-methods approach underpinned by conflicting, and according to some incommensurable, research philosophies. The paper uses some examples from our own experiences of working in interdisciplinary teams to illustrate its potential. DOI: https://doi.org/10.46405/ejms.v3i2.317